The Annual of The NORTH DAKOTA Agricultural College 1914 - New Books - North Dakota Agricultural College (Fargo, N.D.); Fargo (N.D.); (North Dakota State University Library, University Archives;, 1914)
THE 1914 AGASSIZ At Forks Canadians Fargo At Hilsboro New Books Why Fat Men Are Loving - Ethel Poole. How I Got Thin - Olive Porter. Why I Prefer Blonde Men - Edith Shelton. Latest Ideas ln Millinery - Mable Cox. Instructions In Fire Extinguishing - Professors Calnan and Colley My Plans For A Leap Year - Lucy Glacier. Why My Hair ls Red - Eugenia Ruff. Hints On Spooning - Reuben Larson. How I Got My Complexion (ln Verse) - E. D. Sylvester. Extracts From My Sermons - Professor McArdle. How to be Happy Though Married - Professor Hard. How To Run The College - Arthur Ogaard. Beneficial Effects Of Hair Tonic - Ethel Peterson. The Transportation of Infants - Dr. Dolt. How To Make The Men Propose - Beatrice Alm. How To Be Beautiful - Edna Steedsman. Viewbooks; 27 x 20 cm. Title taken from cover of book